Recent developments in enantioselective photocatalysis - Prentice, Callum; Morrisson, James; Smith, Andrew D.; Zysman-Colman, Eli (Beilstein Journal of Organic Chemistry, 2020)
Enantioselective photocatalysis has rapidly grown into a powerful tool for synthetic chemists. This review describes the various strategies for creating enantioenriched products through merging enantioselective catalysis and photocatalysis, with a focus on the most recent developments and a particular interest in the proposed mechanisms for each. With the aim of understanding the scope of each strategy, to help guide and inspire further innovation in this field.
Keywords: enantioenrichment; enantionselective catalysis; enantioselective photocatalysis; photocatalysis; photochemistry

(untitled) - Nicewicz, D. A.; MacMillan, D. W. C. (Science, 2008)

(untitled) - Bauer, A.; Westkämper, F.; Grimme, S.; Bach, T. (Nature, 2005)

Visible Light Photocatalysis in Organic Chemistry - Fensterbank, L.; Goddard, J.-P.; Ollivier, C. (Visible-Light-Mediated Free Radical Synthesis, 2018)

(untitled) - Strieth-Kalthoff, F.; James, M. J.; Teders, M.; Pitzer, L.; Glorius, F. (Chem. Soc. Rev., 2018)

(untitled) - Brimioulle, R.; Lenhart, D.; Maturi, M. M.; Bach, T. (Angew. Chem., Int. Ed., 2015)

(untitled) - Jiang, C.; Chen, W.; Zheng, W.-H.; Lu, H. (Org. Biomol. Chem., 2019)

(untitled) - Seel, C. J.; Gulder, T. (ChemBioChem, 2019)

(untitled) - Brenninger, C.; Jolliffe, J. D.; Bach, T. (Angew. Chem., Int. Ed., 2018)

(untitled) - Huo, H.; Meggersa, E. (Chimia, 2016)

Visible Light Photocatalysis in Organic Chemistry - Coote, S. C.; Bach, T. (Enantioselective Photocatalysis, 2018)

(untitled) - Silvi, M.; Melchiorre, P. (Nature, 2018)

(untitled) - Zou, Y.-Q.; Hörmann, F. M.; Bach, T. (Chem. Soc. Rev., 2018)

(untitled) - Burg, F.; Bach, T. (J. Org. Chem., 2019)

Photochemistry - Holden, C. M.; Melchiorre, P. (Photochemistry and Excited-State Reactivity of Organocatalytic Intermediates, 2019)

(untitled) - Zhang, H.-H.; Chen, H.; Zhu, C.; Yu, S. (Sci. China: Chem., 2020)

(untitled) - Saha, D. (Chem. – Asian J., 2020)

(untitled) - Arokianathar, J. N.; Frost, A. B.; Slawin, A. M. Z.; Stead, D.; Smith, A. D. (ACS Catal., 2018)

(untitled) - Betori, R. C.; May, C. M.; Scheidt, K. A. (Angew. Chem., Int. Ed., 2019)

(untitled) - Rostoll-Berenguer, J.; Blay, G.; Muñoz, M. C.; Pedro, J. R.; Vila, C. (Org. Lett., 2019)

(untitled) - Cismesia, M. A.; Yoon, T. P. (Chem. Sci., 2015)

(untitled) - Bahamonde, A.; Melchiorre, P. (J. Am. Chem. Soc., 2016)

(untitled) - Zhu, Y.; Zhang, L.; Luo, S. (J. Am. Chem. Soc., 2014)

(untitled) - Nagib, D. A.; Scott, M. E.; MacMillan, D. W. C. (J. Am. Chem. Soc., 2009)

(untitled) - Shih, H.-W.; Vander Wal, M. N.; Grange, R. L.; MacMillan, D. W. C. (J. Am. Chem. Soc., 2010)

(untitled) - Welin, E. R.; Warkentin, A. A.; Conrad, J. C.; MacMillan, D. W. C. (Angew. Chem., Int. Ed., 2015)

(untitled) - Gualandi, A.; Marchini, M.; Mengozzi, L.; Kidanu, H. T.; Franc, A.; Ceroni, P.; Cozzi, P. G. (Eur. J. Org. Chem., 2020)

(untitled) - Capacci, A. G.; Malinowski, J. T.; McAlpine, N. J.; Kuhne, J.; MacMillan, D. W. C. (Nat. Chem., 2017)

(untitled) - Yang, Q.; Zhang, L.; Ye, C.; Luo, S.; Wu, L.-Z.; Tung, C.-H. (Angew. Chem., Int. Ed., 2017)

(untitled) - Dong, C.-L.; Ding, X.; Huang, L.-Q.; He, Y.-H.; Guan, Z. (Org. Lett., 2020)

(untitled) - Yang, X.; Xie, Z.; Li, Y.; Zhang, Y. (Chem. Sci., 2020)

(untitled) - Rigotti, T.; Casado-Sánchez, A.; Cabrera, S.; Pérez-Ruiz, R.; Liras, M.; de la Peña O’Shea, V. A.; Alemán, J. (ACS Catal., 2018)

(untitled) - Arceo, E.; Jurberg, I. D.; Álvarez-Fernández, A.; Melchiorre, P. (Nat. Chem., 2013)

(untitled) - Arceo, E.; Bahamonde, A.; Bergonzini, G.; Melchiorre, P. (Chem. Sci., 2014)

(untitled) - Crisenza, G. E. M.; Mazzarella, D.; Melchiorre, P. (J. Am. Chem. Soc., 2020)

(untitled) - Silvi, M.; Arceo, E.; Jurberg, I. D.; Cassani, C.; Melchiorre, P. (J. Am. Chem. Soc., 2015)

(untitled) - Filippini, G.; Silvi, M.; Melchiorre, P. (Angew. Chem., Int. Ed., 2017)

(untitled) - Narayanam, J. M. R.; Tucker, J. W.; Stephenson, C. R. J. (J. Am. Chem. Soc., 2009)

(untitled) - Freeman, D. B.; Furst, L.; Condie, A. G.; Stephenson, C. R. J. (Org. Lett., 2012)

(untitled) - Murphy, J. J.; Bastida, D.; Paria, S.; Fagnoni, M.; Melchiorre, P. (Nature, 2016)

(untitled) - Zhao, J.-J.; Zhang, H.-H.; Shen, X.; Yu, S. (Org. Lett., 2019)

(untitled) - Cao, Z.-Y.; Ghosh, T.; Melchiorre, P. (Nat. Commun., 2018)

(untitled) - Silvi, M.; Verrier, C.; Rey, Y. P.; Buzzetti, L.; Melchiorre, P. (Nat. Chem., 2017)

(untitled) - Mazzarella, D.; Crisenza, G. E. M.; Melchiorre, P. (J. Am. Chem. Soc., 2018)

(untitled) - Verrier, C.; Alandini, N.; Pezzetta, C.; Moliterno, M.; Buzzetti, L.; Hepburn, H. B.; Vega-Peñaloza, A.; Silvi, M.; Melchiorre, P. (ACS Catal., 2018)

(untitled) - Goti, G.; Bieszczad, B.; Vega‐Peñaloza, A.; Melchiorre, P. (Angew. Chem., 2019)

(untitled) - Bonilla, P.; Rey, Y. P.; Holden, C. M.; Melchiorre, P. (Angew. Chem., Int. Ed., 2018)

(untitled) - Perego, L. A.; Bonilla, P.; Melchiorre, P. (Adv. Synth. Catal., 2020)

(untitled) - Hörmann, F. M.; Kerzig, C.; Chung, T. S.; Bauer, A.; Wenger, O. S.; Bach, T. (Angew. Chem., Int. Ed., 2020)

(untitled) - Rigotti, T.; Mas-Ballesté, R.; Alemán, J. (ACS Catal., 2020)

(untitled) - Wei, G.; Zhang, C.; Bureš, F.; Ye, X.; Tan, C.-H.; Jiang, Z. (ACS Catal., 2016)

(untitled) - DiRocco, D. A.; Rovis, T. (J. Am. Chem. Soc., 2012)

(untitled) - Lathrop, S. P.; Rovis, T. (Chem. Sci., 2013)

(untitled) - Dai, L.; Ye, S. (Org. Lett., 2020)

(untitled) - Dai, L.; Xia, Z.-H.; Gao, Y.-Y.; Gao, Z.-H.; Ye, S. (Angew. Chem., Int. Ed., 2019)

(untitled) - Yang, W.; Hu, W.; Dong, X.; Li, X.; Sun, J. (Angew. Chem., Int. Ed., 2016)

(untitled) - Mavroskoufis, A.; Rajes, K.; Golz, P.; Agrawal, A.; Ruß, V.; Götze, J. P.; Hopkinson, M. N. (Angew. Chem., Int. Ed., 2020)

(untitled) - Rono, L. J.; Yayla, H. G.; Wang, D. Y.; Armstrong, M. F.; Knowles, R. R. (J. Am. Chem. Soc., 2013)

(untitled) - Li, S.; Xiang, S.-H.; Tan, B. (Chin. J. Chem., 2020)

(untitled) - Proctor, R. S. J.; Davis, H. J.; Phipps, R. J. (Science, 2018)

(untitled) - Yin, Y.; Dai, Y.; Jia, H.; Li, J.; Bu, L.; Qiao, B.; Zhao, X.; Jiang, Z. (J. Am. Chem. Soc., 2018)

(untitled) - Cao, K.; Tan, S. M.; Lee, R.; Yang, S.; Jia, H.; Zhao, X.; Qiao, B.; Jiang, Z. (J. Am. Chem. Soc., 2019)

(untitled) - Liu, X.; Liu, Y.; Chai, G.; Qiao, B.; Zhao, X.; Jiang, Z. (Org. Lett., 2018)

(untitled) - Zheng, D.; Studer, A. (Angew. Chem., Int. Ed., 2019)

(untitled) - Qiao, B.; Li, C.; Zhao, X.; Yin, Y.; Jiang, Z. (Chem. Commun., 2019)

(untitled) - Shao, T.; Li, Y.; Ma, N.; Li, C.; Chai, G.; Zhao, X.; Qiao, B.; Jiang, Z. (iScience, 2019)

(untitled) - Li, J.; Kong, M.; Qiao, B.; Lee, R.; Zhao, X.; Jiang, Z. (Nat. Commun., 2018)

(untitled) - Zeng, G.; Li, Y.; Qiao, B.; Zhao, X.; Jiang, Zhiyong (Chem. Commun., 2019)

(untitled) - Liu, Y.; Liu, X.; Li, J.; Zhao, X.; Qiao, B.; Jiang, Z. (Chem. Sci., 2018)

(untitled) - Shao, T.; Yin, Y.; Lee, R.; Zhao, X.; Chai, G.; Jiang, Z. (Adv. Synth. Catal., 2018)

(untitled) - Li, J.; Gu, Z.; Zhao, X.; Qiao, B.; Jiang, Z. (Chem. Commun., 2019)

(untitled) - Cheng, Y.-Z.; Zhao, Q.-R.; Zhang, X.; You, S.-L. (Angew. Chem., Int. Ed., 2019)

(untitled) - Pecho, F.; Zou, Y.-Q.; Gramüller, J.; Mori, T.; Huber, S. M.; Bauer, A.; Gschwind, R. M.; Bach, T. (Chem. – Eur. J., 2020)

(untitled) - Lian, M.; Li, Z.; Cai, Y.; Meng, Q.; Gao, Z. (Chem. – Asian J., 2012)

(untitled) - Wang, Y.; Zheng, Z.; Lian, M.; Yin, H.; Zhao, J.; Meng, Q.; Gao, Z. (Green Chem., 2016)

(untitled) - Wang, Y.; Yin, H.; Tang, X.; Wu, Y.; Meng, Q.; Gao, Z. (J. Org. Chem., 2016)

(untitled) - Tang, X.-F.; Zhao, J.-N.; Wu, Y.-F.; Zheng, Z.-H.; Feng, S.-H.; Yu, Z.-Y.; Liu, G.-Z.; Meng, Q.-W. (Org. Biomol. Chem., 2019)

(untitled) - Woźniak, Ł.; Murphy, J. J.; Melchiorre, P. (J. Am. Chem. Soc., 2015)

(untitled) - Cauble, D. F.; Lynch, V.; Krische, M. J. (J. Org. Chem., 2003)

(untitled) - Müller, C.; Bauer, A.; Bach, T. (Angew. Chem., Int. Ed., 2009)

(untitled) - Müller, C.; Bauer, A.; Maturi, M. M.; Cuquerella, M. C.; Miranda, M. A.; Bach, T. (J. Am. Chem. Soc., 2011)

(untitled) - Alonso, R.; Bach, T. (Angew. Chem., Int. Ed., 2014)

(untitled) - Maturi, M. M.; Bach, T. (Angew. Chem., Int. Ed., 2014)

(untitled) - Tröster, A.; Alonso, R.; Bauer, A.; Bach, T. (J. Am. Chem. Soc., 2016)

(untitled) - Li, X.; Jandl, C.; Bach, T. (Org. Lett., 2020)

(untitled) - Hölzl-Hobmeier, A.; Bauer, A.; Silva, A. V.; Huber, S. M.; Bannwarth, C.; Bach, T. (Nature, 2018)

(untitled) - Plaza, M.; Jandl, C.; Bach, T. (Angew. Chem., Int. Ed., 2020)

(untitled) - Wimberger, L.; Kratz, T.; Bach, T. (Synthesis, 2019)

(untitled) - Tröster, A.; Bauer, A.; Jandl, C.; Bach, T. (Angew. Chem., Int. Ed., 2019)

(untitled) - Vallavoju, N.; Selvakumar, S.; Jockusch, S.; Sibi, M. P.; Sivaguru, J. (Angew. Chem., Int. Ed., 2014)

(untitled) - Skubi, K. L.; Kidd, J. B.; Jung, H.; Guzei, I. A.; Baik, M.-H.; Yoon, T. P. (J. Am. Chem. Soc., 2017)

(untitled) - Skubi, K. L.; Swords, W. B.; Hofstetter, H.; Yoon, T. P. (ChemPhotoChem, 2020)

(untitled) - Zheng, J.; Swords, W. B.; Jung, H.; Skubi, K. L.; Kidd, J. B.; Meyer, G. J.; Baik, M.-H.; Yoon, T. P. (J. Am. Chem. Soc., 2019)

(untitled) - Liu, Y.; Li, J.; Ye, X.; Zhao, X.; Jiang, Z. (Chem. Commun., 2016)

(untitled) - Griffiths, J.; Chu, K.-Y.; Hawkins, C. (J. Chem. Soc., Chem. Commun., 1976)

(untitled) - Hou, M.; Lin, L.; Chai, X.; Zhao, X.; Qiao, B.; Jiang, Z. (Chem. Sci., 2019)

(untitled) - Lin, L.; Bai, X.; Ye, X.; Zhao, X.; Tan, C.-H.; Jiang, Z. (Angew. Chem., Int. Ed., 2017)

(untitled) - Shin, N. Y.; Ryss, J. M.; Zhang, X.; Miller, S. J.; Knowles, R. R. (Science, 2019)

(untitled) - Roos, C. B.; Demaerel, J.; Graff, D. E.; Knowles, R. R. (J. Am. Chem. Soc., 2020)

(untitled) - Shen, M.-L.; Shen, Y.; Wang, P.-S. (Org. Lett., 2019)

(untitled) - Uraguchi, D.; Kinoshita, N.; Kizu, T.; Ooi, T. (J. Am. Chem. Soc., 2015)

(untitled) - Yang, Z.; Li, H.; Li, S.; Zhang, M.-T.; Luo, S. (Org. Chem. Front., 2017)

(untitled) - Hamilton, D. S.; Nicewicz, D. A. (J. Am. Chem. Soc., 2012)

(untitled) - Gentry, E. C.; Rono, L. J.; Hale, M. E.; Matsuura, R.; Knowles, R. R. (J. Am. Chem. Soc., 2018)

(untitled) - Morse, P. D.; Nguyen, T. M.; Cruz, C. L.; Nicewicz, D. A. (Tetrahedron, 2018)

(untitled) - Mukaiyama, T.; Narasaka, K.; Banno, K. (Chem. Lett., 1973)

(untitled) - Wadamoto, M.; Ozasa, N.; Yanagisawa, A.; Yamamoto, H. (J. Org. Chem., 2003)

(untitled) - Du, J.; Skubi, K. L.; Schultz, D. M.; Yoon, T. P. (Science, 2014)

(untitled) - Amador, A. G.; Sherbrook, E. M.; Yoon, T. P. (J. Am. Chem. Soc., 2016)

(untitled) - Ruiz Espelt, L.; McPherson, I. S.; Wiensch, E. M.; Yoon, T. P. (J. Am. Chem. Soc., 2015)

(untitled) - Ruiz Espelt, L.; Wiensch, E. M.; Yoon, T. P. (J. Org. Chem., 2013)

(untitled) - Pagire, S. K.; Kumagai, N.; Shibasaki, M. (Chem. Sci., 2020)

(untitled) - Ye, C.-X.; Melcamu, Y. Y.; Li, H.-H.; Cheng, J.-T.; Zhang, T.-T.; Ruan, Y.-P.; Zheng, X.; Lu, X.; Huang, P.-Q. (Nat. Commun., 2018)

(untitled) - Miller, Z. D.; Lee, B. J.; Yoon, T. P. (Angew. Chem., Int. Ed., 2017)

(untitled) - Blum, T. R.; Miller, Z. D.; Bates, D. M.; Guzei, I. A.; Yoon, T. P. (Science, 2016)

(untitled) - Huo, H.; Harms, K.; Meggers, E. (J. Am. Chem. Soc., 2016)

(untitled) - Steinlandt, P. S.; Zuo, W.; Harms, K.; Meggers, E. (Chem. – Eur. J., 2019)

(untitled) - Huang, X.; Webster, R. D.; Harms, K.; Meggers, E. (J. Am. Chem. Soc., 2016)

(untitled) - Kuang, Y.; Wang, K.; Shi, X.; Huang, X.; Meggers, E.; Wu, J. (Angew. Chem., Int. Ed., 2019)

(untitled) - Huang, X.; Lin, J.; Shen, T.; Harms, K.; Marchini, M.; Ceroni, P.; Meggers, E. (Angew. Chem., Int. Ed., 2018)

(untitled) - Huang, X.; Meggers, E. (Acc. Chem. Res., 2019)

(untitled) - Liang, H.; Xu, G.-Q.; Feng, Z.-T.; Wang, Z.-Y.; Xu, P.-F. (J. Org. Chem., 2019)

(untitled) - Zhou, Z.; Nie, X.; Harms, K.; Riedel, R.; Zhang, L.; Meggers, E. (Sci. China: Chem., 2019)

(untitled) - Zhang, C.; Chen, S.; Ye, C.-X.; Harms, K.; Zhang, L.; Houk, K. N.; Meggers, E. (Angew. Chem., Int. Ed., 2019)

(untitled) - Zhang, K.; Lu, L.-Q.; Jia, Y.; Wang, Y.; Lu, F.-D.; Pan, F.; Xiao, W.-J. (Angew. Chem., Int. Ed., 2019)

(untitled) - Ding, W.; Lu, L.-Q.; Zhou, Q.-Q.; Wei, Y.; Chen, J.-R.; Xiao, W.-J. (J. Am. Chem. Soc., 2017)

(untitled) - Liu, J.; Ding, W.; Zhou, Q.-Q.; Liu, D.; Lu, L.-Q.; Xiao, W.-J. (Org. Lett., 2018)

(untitled) - Li, Y.; Zhou, K.; Wen, Z.; Cao, S.; Shen, X.; Lei, M.; Gong, L. (J. Am. Chem. Soc., 2018)

(untitled) - Han, B.; Li, Y.; Yu, Y.; Gong, L. (Nat. Commun., 2019)

(untitled) - Li, Y.; Lei, M.; Gong, L. (Nat. Catal., 2019)

(untitled) - Lewis, F. D.; Howard, D. K.; Oxman, J. D. (J. Am. Chem. Soc., 1983)

(untitled) - Lewis, F. D.; Barancyk, S. V. (J. Am. Chem. Soc., 1989)

(untitled) - Guo, H.; Herdtweck, E.; Bach, T. (Angew. Chem., Int. Ed., 2010)

(untitled) - Brimioulle, R.; Bauer, A.; Bach, T. (J. Am. Chem. Soc., 2015)

(untitled) - Brimioulle, R.; Bach, T. (Science, 2013)

(untitled) - Poplata, S.; Bach, T. (J. Am. Chem. Soc., 2018)

(untitled) - Stegbauer, S.; Jandl, C.; Bach, T. (Angew. Chem., Int. Ed., 2018)

(untitled) - Leverenz, M.; Merten, C.; Dreuw, A.; Bach, T. (J. Am. Chem. Soc., 2019)

(untitled) - Daub, M. E.; Jung, H.; Lee, B. J.; Won, J.; Baik, M.-H.; Yoon, T. P. (J. Am. Chem. Soc., 2019)

(untitled) - De Abreu, M.; Belmont, P.; Brachet, E. (Eur. J. Org. Chem., 2020)

(untitled) - Twilton, J.; Le, C.; Zhang, P.; Shaw, M. H.; Evans, R. W.; MacMillan, D. W. C. (Nat. Rev. Chem., 2017)

(untitled) - Gui, Y.-Y.; Sun, L.; Lu, Z.-P.; Yu, D.-G. (Org. Chem. Front., 2016)

(untitled) - Tellis, J. C.; Kelly, C. B.; Primer, D. N.; Jouffroy, M.; Patel, N. R.; Molander, G. A. (Acc. Chem. Res., 2016)

(untitled) - Zuo, Z.; Cong, H.; Li, W.; Choi, J.; Fu, G. C.; MacMillan, D. W. C. (J. Am. Chem. Soc., 2016)

(untitled) - Cheng, X.; Lu, H.; Lu, Z. (Nat. Commun., 2019)

(untitled) - Pezzetta, C.; Bonifazi, D.; Davidson, R. W. M. (Org. Lett., 2019)

(untitled) - Shen, Y.; Gu, Y.; Martin, R. (J. Am. Chem. Soc., 2018)

(untitled) - Stache, E. E.; Rovis, T.; Doyle, A. G. (Angew. Chem., Int. Ed., 2017)

(untitled) - Guan, H.; Zhang, Q.; Walsh, P. J.; Mao, J. (Angew. Chem., Int. Ed., 2020)

(untitled) - Rand, A. W.; Yin, H.; Xu, L.; Giacoboni, J.; Martin-Montero, R.; Romano, C.; Montgomery, J.; Martin, R. (ACS Catal., 2020)

(untitled) - Esposti, S.; Dondi, D.; Fagnoni, M.; Albini, A. (Angew. Chem., Int. Ed., 2007)

(untitled) - Fan, P.; Lan, Y.; Zhang, C.; Wang, C. (J. Am. Chem. Soc., 2020)

(untitled) - Perry, I. B.; Brewer, T. F.; Sarver, P. J.; Schultz, D. M.; DiRocco, D. A.; MacMillan, D. W. C. (Nature, 2018)

(untitled) - Yuan, M.; Song, Z.; Badir, S. O.; Molander, G. A.; Gutierrez, O. (J. Am. Chem. Soc., 2020)

(untitled) - Kainz, Q. M.; Matier, C. D.; Bartoszewicz, A.; Zultanski, S. L.; Peters, J. C.; Fu, G. C. (Science, 2016)

(untitled) - Zhang, Y.; Sun, Y.; Chen, B.; Xu, M.; Li, C.; Zhang, D.; Zhang, G. (Org. Lett., 2020)

(untitled) - Wang, D.; Zhu, N.; Chen, P.; Lin, Z.; Liu, G. (J. Am. Chem. Soc., 2017)

(untitled) - Zhang, W.; Wang, F.; McCann, S. D.; Wang, D.; Chen, P.; Stahl, S. S.; Liu, G. (Science, 2016)

(untitled) - Lu, F.-D.; Liu, D.; Zhu, L.; Lu, L.-Q.; Yang, Q.; Zhou, Q.-Q.; Wei, Y.; Lan, Y.; Xiao, W.-J. (J. Am. Chem. Soc., 2019)

(untitled) - Chen, J.; Wang, P.-Z.; Lu, B.; Liang, D.; Yu, X.-Y.; Xiao, W.-J.; Chen, J.-R. (Org. Lett., 2019)

(untitled) - Sha, W.; Deng, L.; Ni, S.; Mei, H.; Han, J.; Pan, Y. (ACS Catal., 2018)

(untitled) - Guo, Q.; Wang, M.; Peng, Q.; Huo, Y.; Liu, Q.; Wang, R.; Xu, Z. (ACS Catal., 2019)

(untitled) - Zhang, H.-H.; Zhao, J.-J.; Yu, S. (J. Am. Chem. Soc., 2018)

(untitled) - Zhang, H.-H.; Zhao, J.-J.; Yu, S. (ACS Catal., 2020)

(untitled) - Shen, D.; Saracini, C.; Lee, Y.-M.; Sun, W.; Fukuzumi, S.; Nam, W. (J. Am. Chem. Soc., 2016)

(untitled) - Mitsunuma, H.; Tanabe, S.; Fuse, H.; Ohkubo, K.; Kanai, M. (Chem. Sci., 2019)

Enzyme Catalysis in Organic Synthesis - Bornscheuer, U. T.; Kazlauskas, R. J. (Enzymatic Catalytic Promiscuity and the Design of New Enzyme Catalyzed Reactions, 2012)

(untitled) - Emmanuel, M. A.; Greenberg, N. R.; Oblinsky, D. G.; Hyster, T. K. (Nature, 2016)

(untitled) - Biegasiewicz, K. F.; Cooper, S. J.; Gao, X.; Oblinsky, D. G.; Kim, J. H.; Garfinkle, S. E.; Joyce, L. A.; Sandoval, B. A.; Scholes, G. D.; Hyster, T. K. (Science, 2019)

(untitled) - Guo, X.; Okamoto, Y.; Schreier, M. R.; Ward, T. R.; Wenger, O. S. (Chem. Sci., 2018)

(untitled) - Litman, Z. C.; Wang, Y.; Zhao, H.; Hartwig, J. F. (Nature, 2018)

(untitled) - Biegasiewicz, K. F.; Cooper, S. J.; Emmanuel, M. A.; Miller, D. C.; Hyster, T. K. (Nat. Chem., 2018)

(untitled) - Nakano, Y.; Black, M. J.; Meichan, A. J.; Sandoval, B. A.; Chung, M. M.; Biegasiewicz, K. F.; Zhu, T.; Hyster, T. K. (Angew. Chem., Int. Ed., 2020)

(untitled) - Ding, X.; Dong, C.-L.; Guan, Z.; He, Y.-H. (Angew. Chem., Int. Ed., 2019)

Enzyme Catalysis in Organic Synthesis - van den Wittenboer, A.; Hilterhaus, L.; Liese, A. (Industrial Applications of Enzymes in Emerging Areas, 2012)

(untitled) - Yang, Q.; Zhao, F.; Zhang, N.; Liu, M.; Hu, H.; Zhang, J.; Zhou, S. (Chem. Commun., 2018)

(untitled) - Ener, M. E.; Lee, Y.-T.; Winkler, J. R.; Gray, H. B.; Cheruzel, L. (Proc. Natl. Acad. Sci. U. S. A., 2010)

(untitled) - Tran, N.-H.; Nguyen, D.; Dwaraknath, S.; Mahadevan, S.; Chavez, G.; Nguyen, A.; Dao, T.; Mullen, S.; Nguyen, T.-A.; Cheruzel, L. E. (J. Am. Chem. Soc., 2013)

(untitled) - Sosa, V.; Melkie, M.; Sulca, C.; Li, J.; Tang, L.; Li, J.; Faris, J.; Foley, B.; Banh, T.; Kato, M.; Cheruzel, L. E. (ACS Catal., 2018)